Treatment of polyglandular autoimmune syndrome type 3 using co-transplantation of insulin-secreting mesenchymal stem cells and haematopoietic stem cells - Trivedi, Hargovind L (BMJ Publishing Group, 2011)
The authors report a 17-year-female and a 19-year-male with uncontrolled insulin-dependent diabetes mellitus (IDDM) for ≥10 years, treated with insulin-secreting human adipose tissue derived mesenchymal stem cells (IS-h-ADMSC). Both had hypothyroidism and were diagnosed as polyglandular autoimmune syndrome type-3 (PGAS-3). PGAS are rare polyendocrinopathies with ≥2 endocrine disorders mediated by autoimmune mechanisms leading to hypo-function and organ failure. Therapeutic options are hormone replacement, immunosuppression and avoiding infection. The authors administered autologous H-AD-IS-MSC+bone marrow-derived haematopoietic stem cells (HSC) into portal circulation with conditioning of cyclophosphamide, bortezomib, rituximab and rabbit-antithymoglobulin. Over follow-up of 38 and 16 months, respectively, both are doing well with sustained fall of glycosylated haemoglobin (Hb1Ac) from 8.1 to 6.4% and 14.2 to 8.6%, respectively and C-peptide raised from 0.01 to 0.23 ng/ml and 0.1 to 0.34 ng/ml, respectively with sustained 40% decreased insulin requirement. Thus long-term control of IDDM in PGAS-3 with co-transplantation of H-AD-IS-MSC+HSC can be achieved safely and effectively.